Ambientación y adecuación de la sala de exposiciones en el centro recreacional “Padre Eliseo Arias Carrión”, para exposición y venta de artesanías - Valarezo Patiño, Cristian Patricio (2015)
This research project has been set and decorated the exhibition hall at the Recreation Complex Father Eliseo Arias Carrion (Guayabal), it has been applied in order rustic style that fits the current environment. For this it was necessary to investigate the theoretical concepts related to the topic, such as anthropometric data, luminaries, etc. for proper implementation and application in different spaces in general. As for the interior decoration it has been applied light colors creating a feeling of spaciousness, as brown hues in certain areas, wooden beams; like decorative details such as stone columns view Taper, Achieving an elegant and rustic space. Regarding the furniture that will be designed wood and glass, to highlight the exhibition of paintings and handicrafts in the different areas has been implemented direct and indirect lighting (spotlights on rails electrified) giving spot lighting objects and large windows capable to provide income to natural lighting. The proposal has been designed with the opportunity to emphasize the use of natural materials in the rustic style gained a good atmosphere and distributing it. Realizing a vision of the interior routes, its furnishings and colors in different environments giving a new and innovative proposal in this style